How to Estimate the Binder: Aggregate Ratio From Lime-Based Historic Mortars for Restoration? - Loureiro, Alexandre Máximo Silva; Paz, Simone Patrícia Aranha da; Angélica, Rômulo Simões (Frontiers in Materials, 2020)
One of the most important studies from historic mortars is the binder:aggregate ratio, which is usually obtained through wet chemical analysis. Instrumental techniques and benchtop equipment have become increasingly important tools in the characterization of historic materials. The analysis of such materials has become more practical, faster and more accurate, and the sample preparation methods require less and less material. Thus, this article aims to investigate the validity of the results obtained by some of the methods and techniques used in historic materials analysis and determine the possibility of estimating the binder:aggregate ratio with adequate accuracy and precision. For this purpose, historic mortars from Belém do Pará, in northern Brazil, were selected, and the following quantification techniques were employed: wet chemical analysis, XRD, DSC and XRF. The results showed that the amounts of the components in the mortars could be quantified with the use of approximately three grams of sample, thus providing one of the main pieces of information needed for the production of a restoration mortar: the binder:aggregate ratio.